THE RELATIONSHIP BETWEEN PROGNOSTIC FACTORS AND TREATMENT OUTCOME OF MULTIPLE MYELOMA (Vietnam Journal of Community Medicine, 2022)
Objectives: To analyze the relationship between prognostic factors to outcomes ofnumber of multiple myeloma (MM) treatment regimens at Ho Chi Minh city (HCMC)Blood Transfusion and Hematology Hospital from 2018 to 2021.Subjects and methods: A descriptive and analytical study on 111 patients newlydiagnosed with MM from January 2018 to December 2021 according to IMWG 2014standards who came for examination and treatment at HCMC Blood Transfusion andHematology Hospital.Results: The prognostic factors associated with statistical significance to the rate ofat least very good partial response (VGPR) compared with the other group including:Clinical index ECOG < 2, NLR < 2.25, platelet ≥ 150, novel treatment regimen andmyeloma prognostic index (MPI).Conclusion: Clinical index ECOG < 2, NLR < 2.25, platelet ≥ 150, new treatmentregimen and MPI were the prognostic factors associated with MM.
Keywords: Multiple myeloma, prognostic factors, relationship.